Projeto North Atlantic Security and Defense Strategy (NASDS) - Marsili, M. (IUM Atualidade, 2022)
The NASDS project aims to investigate the issues related to the security and defense of maritime space and sea routes from the Arctic Ocean to the North Atlantic, including the control of search and rescue (SAR) areas through unmanned autonomous systems.